Illegal fishing at Isla del Coco National Park, Costa Rica. - López-Garro, Andrés; Zanella, Ilena; Martínez, Frank; Golfín-Duarte, Geiner; Pérez-Montero, Maikel (Revista de Biología Tropical, 2016)
Isla del Coco National Park (ICNP), Costa Rica, is renowned for its large aggregations of pelagic species, especially sharks (Carcharhinidae and Sphyrnidae), billfish (Istiophoridae) and tuna (Scombridae). The high abundance of these sought after species, attracts commercial fishing vessels that enter the protected waters of the Park. Illegal fisheries thus represent one of the biggest threats to the ecological integrity of this World Heritage Site. The ICNP dedicates important resources to protection and control via regular surveillance patrols, along the 12 nautical miles that have Marine Protected Area (MPA) status. During 2012, 2013 and between January and August 2014, 405 surveillance patrols within the MPA found 108 fishing lines, more than 13 000 hooks, seized more than 500 km of fishing line and 257 pelagic individuals. The yellowfin tuna (Thunnus albacares) was the most abundant species, representing more than 72.3 % of the total catch; seized individuals had a mean total length of 153.35±23.19 cm (Min=90 cm; Max=190 cm); which indicates that most individuals were adults. Analysis of monthly CPUE showed that the highest relative abundance of illegally caught T. albacores was between May and August of each year, with a mean relative abundance of 26.13±54.71, 11.63±23.79, 13.71±24.52 tunas per 1 000 hooks in 2012, 2013, 2014, respectively. This species had a high survival rate (nearly 80 % of the individuals found on the lines were still alive), probably due to the short fishing lines used by illegal fishermen, combined with the swift intervention of rangers. The CPUE of T. albacares found in this study is greater than records in Costa Rica’s Exclusive Economic Zone (0.74 and 0.44 per 1 000 hooks respectively). These results highlight the importance of ICNP as an aggregation site for T. albacares and the need for its effective protection. It is important that ranger intervention continue to be as rapid and effective as possible, in order to decrease the impact of illegal fishing on the marine biodiversity of the ICNP.